THE EFFECT OF SERVICE QUALITY AND PRICE ON PURCHASE DECISIONS AT D'CREPES PONDOK INDAH MALL SOUTH JAKARTA - Siti Aprilliani (Asosiasi Dosen Muda Indonesia, 2024)
This study aims to analyze the effect of service quality and price on consumer purchase decisions at D'Crepes Pondok Indah Mall, South Jakarta. The research employs a quantitative method with an associative approach, where service quality and price serve as independent variables, and purchase decisions act as the dependent variable. Data was collected through questionnaires distributed to 100 respondents. The findings indicate that both service quality and price significantly influence consumer purchase decisions, both partially and simultaneously. Simple linear regression analysis reveals that service quality has a strong impact on purchase decisions, while price also exerts a considerable influence. Additionally, multiple linear regression confirms that service quality and price together have a very strong correlation with purchase decisions, accounting for 76.4% of the variation in consumer behavior. This research emphasizes the importance of providing high-quality service and setting appropriate prices to improve consumer purchase decisions. However, the study acknowledges several limitations, including the restricted number of variables analyzed and the sole use of questionnaires for data collection. Further studies are recommended to explore additional factors such as location, promotion, and brand image, and to expand the sample size for broader insights.